2020
DOI: 10.1371/journal.pone.0227867
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to met needs for rehabilitation 6 years after stroke

Abstract: Introduction Research on stroke rehabilitation mainly concerns the first year of recovery, and there is a lack of knowledge regarding long-term rehabilitation needs and associated factors. Aim The aim was to explore the perceived needs for rehabilitation services of people six years after stroke and factors associated with having rehabilitation services needs met. Methods The study was a 6-year follow up of a prospective study on the rehabilitation process after stroke. Data on perceived needs for rehabilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
1
6
0
1
Order By: Relevance
“…Our findings suggest that fatigue is the most prominent symptom that interferes with many physical functions, including ADLs and mobility, which is not surprising. The results of this study support the findings of Ytterberg et al (2020), who found that patients with stroke continue to feel fatigue long after their brain injury, which continues to impede their mobility. Curiously, we noted that, on admission, our participants were very optimistic about their ability to perform tasks and daily functions; however, their confidence tempered as they spent time in physical, occupational, and speech therapies.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings suggest that fatigue is the most prominent symptom that interferes with many physical functions, including ADLs and mobility, which is not surprising. The results of this study support the findings of Ytterberg et al (2020), who found that patients with stroke continue to feel fatigue long after their brain injury, which continues to impede their mobility. Curiously, we noted that, on admission, our participants were very optimistic about their ability to perform tasks and daily functions; however, their confidence tempered as they spent time in physical, occupational, and speech therapies.…”
Section: Discussionsupporting
confidence: 89%
“…A further need expressed was the appreciation of the importance of any programme being flexible to meet the needs of those with fluctuating energy levels. Many clinicians felt that programmes should address long-term needs of people, a perception in line with the findings of research with longer follow up of people with PSF, which suggests fatigue is a factor for many survivors for many years after their stroke (Duncan et al, 2020;Ytterberg et al, 2020). There was a strong belief across the professional groups that people needed support to self-manage their fatigue.…”
Section: Discussionmentioning
confidence: 91%
“…Participants portrayed the importance of inclusive communication between stroke survivors and the HCPs treating them, where stroke survivors feel their individual needs are considered. This has been reflected elsewhere, as stroke survivors who report a perceived involvement in their care and treatment are associated with reporting their recovery service needs being met ( 87 ). More specifically, met needs have also been associated with shared decision-making in the rehabilitation goal-setting process ( 88 , 89 ).…”
Section: Discussionmentioning
confidence: 92%